Mitochondrial-type iron-sulfur cluster biosynthesis genes (IscS and IscU) in the apicomplexan Cryptosporidium parvum - LaGier, Michael J; Tachezy, Jan; Stejskal, Frantisek; Kutisova, Katerina; Keithly, Janet S (Microbiology (Reading, England), 2003)
Several reports have indicated that the iron-sulfur cluster [Fe-S] assembly machinery in most eukaryotes is confined to the mitochondria and chloroplasts. The best-characterized and most highly conserved [Fe-S] assembly proteins are a pyridoxal-5'-phosphate-dependent cysteine desulfurase (IscS), and IscU, a protein functioning as a scaffold for the assembly of [Fe-S] prior to their incorporation into apoproteins. In this work, genes encoding IscS and IscU homologues have been isolated and characterized from the apicomplexan parasite Cryptosporidium parvum, an opportunistic pathogen in AIDS patients, for which no effective treatment is available. Primary sequence analysis (CpIscS and CpIscU) and phylogenetic studies (CpIscS) indicate that both genes are most closely related to mitochondrial homologues from other organisms. Moreover, the N-terminal signal sequences of CpIscS and CpIscU predicted in silico specifically target green fluorescent protein to the mitochondrial network of the yeast Saccharomyces cerevisiae. Overall, these findings suggest that the previously identified mitochondrial relict of C. parvum may have been retained by the parasite as an intracellular site for [Fe-S] assembly.
Keywords: rekombinantní fúzní proteiny; Genes, Protozoan; Green Fluorescent Proteins; zvířata; Gene Expression; Recombinant Fusion Proteins; fylogeneze; Cryptosporidium parvum; protozoální DNA; klonování DNA; zelené fluorescenční proteiny; DNA, Protozoan; Cloning, Molecular; sekvenční homologie aminokyselin; Protozoan Proteins; Molecular Sequence Data; Phylogeny; Protein Sorting Signals; Animals; proteiny - lokalizační signály; proteiny obsahující železo a síru; molekulární sekvence - údaje; Base Sequence; mitochondrie; Sequence Homology, Amino Acid; Mitochondria; protozoální geny; sekvence aminokyselin; sekvence nukleotidů; exprese genu; Amino Acid Sequence; luminescentní proteiny; Iron-Sulfur Proteins; protozoální proteiny; Luminescent Proteins